Country Business Culture and Influence On International Business Strategy - Devi Pertiwi Ananda Putri; Akhmad Sukardi (University of Science and Computer Technology, 2023)
The purpose of this research is to analyze the business culture of South Korea and its comparison with business culture in Indonesia and its influence on international business strategy. This research uses the Literature Review method using data sources from Google Scholar indexed by Sinta 1-6, and the Copernicus Index and reputable International Journals indexed by Scopus over a 5 year period starting from 2018-2023. Article collection was carried out using the keywords business culture, organizational culture, business strategy. The results of this research show that in South Korean business culture the people are more individualistic and there are two important aspects of business culture in South Korea, namely Kibun and Inhwa. A very clear difference can be seen between South Korean business culture, which tends to be individualistic, and Indonesian business culture, which is closely related to family values and togetherness in making business decisions. From these cultural differences, international business companies need to understand the characteristics of each business culture of the country in which they do business in order to determine a business strategy that suits the business culture prevailing in that country.